Strategic approaches to value investing: a systematic literature review of international studies. Issue 3 (2nd September 2019) - Battisti, Enrico; Miglietta, Nicola; Salvi, Antonio; Creta, Fabio
Abstract : Purpose: This paper aims to present a systematic literature review (SRL) on the topic of value investing (VI) in the international studies. The purpose of this study is twofold: to highlight the strategic approaches followed in recent contributions in the field of finance connected to the main approaches of the pioneering authors (Graham and Dodd, 1934; Fisher, 1958; Fama and French, 1992; Lakonishok, Shleifer and Vishny, 1994) who have investigated VI; and to analyse whether scholars follow a qualitative approach in studying VI that enables companies to achieve greater competitive advantage.. Design/methodology/approach: From a SLR of peer-reviewed papers covering the period 2007-2017, 45 papers were identified and analysed to present a better understanding of the adopted approaches and methodologies compared to the pioneering contributions on the topic. Findings: This search found that 24 out of 45 papers specifically analyse VI. In particular, this work highlights 20 out of 24 papers that directly or indirectly, follow the approaches of "Graham and Dodd" or "Lakonishok, Shleifer and Vishny"/"Fama and French", and 4 out of 24 that do not follow one of the main approaches identified. After the descriptive findings of the review, this paper highlights that none of the contributions takes into account qualitative analysis of a company to define whether the firm itself does or does not have a sustainable competitive advantage. Practical implications: This paper suggests to international investors who intend to invest in one or more markets to revise the basic principles of VI, while also considering qualitative elements related to strategic aspects and behavioural finance. In particular, this study suggests that the investor introduce a qualitative analysis to allocate equity in value firms with a lasting competitive advantage. Originality/value: This study contributes to advance the knowledge of VI from a theoretical point of view. To the best of the authors' knowledge, it is the first study that systematises the international literature on this topic by highlighting the main contributions written in the period 2007-2017, analysing the development of the pioneering strategic approaches and examining their method of assessing firms.